Role of CD117 and mast cells in periodontal diseases: Histological and immunohistochemical study - Fatin L. Khaphi; Hanaa Ali Hussein; Oula Fouad Hameed; Huda Jassem Jebur; Zahra Kadhum Saeed (Journal of Advanced Biotechnology and Experimental Therapeutics)
Mast cells are mobile secretory cells with a variety of biological tasks such as phagocytosis, processing of antigens, cytokine production, and the release of both newly formed and preexisting physiological mediators. This study aimed to investigate and establish the relationship between mast cells and various stages of periodontal diseases. A total of 36 soft tissue samples, 12 each of normal healthy periodontal, dental plaque periodontitis, and chronic periodontitis were selected. Samples were collected from patients with periodontal surgery in chronic periodontitis and plaque periodontitis. Samples were stained with 1% toluidine blue (TB), immunohistochemistry for CD117 expression, and observed under a light microscope for the presence of mast cells. All data were analyzed using SPSS. The mast cells were found to be highest in the chronic periodontitis group, followed by the dental plaque periodontitis group, as compared to the healthy periodontal group. The quantitative study of mast cells using TB staining showed statistically significant differences among the three groups. However, the results showed no statistically significant difference in the expression levels of CD117 in the plaque periodontitis and healthy periodontal group but showed a statistically significant difference between chronic periodontitis and healthy periodontal group. Thus, an increase in mast cells in human periodontal diseases suggests that these cells are crucial for developing chronic periodontitis. [ J Adv Biotechnol Exp Ther 2025; 8(1.000): 182-191]